2021
DOI: 10.3390/polym13223863
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Resin Cement Thickness and Elastic Modulus on the Stress Distribution of Zirconium Dioxide Inlay-Bridge: 3D Finite Element Analysis

Abstract: The mechanical properties and the thickness of the resin cement agents used for bonding inlay bridges can modify the clinical performance of the restoration such as debonding or prosthetic materials fracture. Thus, the aim of this study was to evaluate the stress distribution and the maximum strain generated by resin cements with different elastic moduli and thicknesses used to cement resin-bonded fixed partial denture (RBFPD). A three-dimensional (3D) finite element analysis (FEA) was used, and a 3D model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…According to the literature, intraoral bite forces range from 216 to 847 N [6]. The mean unilateral bite force in the premolar area is 70% lower than that in the molar region, with an average of 210-420 N [40,41]. In another study [19], it was reported that the mean maximum bite force was approximately 353 N in males; meanwhile, it was 218 N in females.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, intraoral bite forces range from 216 to 847 N [6]. The mean unilateral bite force in the premolar area is 70% lower than that in the molar region, with an average of 210-420 N [40,41]. In another study [19], it was reported that the mean maximum bite force was approximately 353 N in males; meanwhile, it was 218 N in females.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors influence the fracture strength of prostheses, including the force of applied load, cement type and technique, and elastic modulus of supporting structure. Using a supporting material with a high elastic modulus can increase fracture resistance [42]. The fracture strength of a dental restoration could be more accurate if natural teeth were used as a supporting model [32,39].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the intraoral bite forces are in the range of 216-847 N [9,50]. The mean unilateral bite force in the premolar area is 70% lower than the molar region, with an average of 210-420 N [42]. In another study [51], the mean value of the maximum bite force is around 353 N in men, while in women it is 218 N. In one study [50] discussing the effect of clenching intensity on the biting force in the premolar region, the results showed values from 450 to 660 N. According to our results, these designs cannot be used in case of clenching and bruxism.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, a special library for the materials included in the study was created by engineering data from the components' systems, but later, the library was modified from engineering data sources, and the materials and their properties were inserted (Young's modulus and Poisson's modulus) as shown in Table 4 Indirect composite 16 x 10 3 0.24 [10] Ceramic reinforced with lithium disilicate 83.5 x 10 3 0.21 [11] Porcelain fused to metal 68.9 x 10 3 0.28 [12] Zirconia 210 x 10 3 0.30 [12] Luting cement 12 x 10 3 0.24 [13] Adhesive layer 3 x 10 3 0.30 [14] TABLE 4: The characteristics of the studied materials…”
Section: Analysis System (Ansys) Programmentioning
confidence: 99%